Deconstructing Arabic Language Instruction: A Love-Based Curriculum Approach to Mitigating Foreign Language Anxiety - Habib Maulana Maslahul Adi (JPT : Jurnal Pendidikan Tematik, 2026)
Arabic language learning is often trapped in mechanical approaches and rigid grammatical formalism, triggering high levels of Foreign Language Anxiety (FLA) among students. This psycholinguistic phenomenon results in an elevated affective filter, which significantly hinders working memory capacity and the natural language acquisition process. This conceptual article aims to deconstruct the traditional learning paradigm by proposing a Love-Based Curriculum approach as a pedagogical solution. Utilizing a library research method with a traditional literature review, this study synthesizes modern psycholinguistic literature and classical Islamic educational philosophy. The findings indicate that reducing FLA cannot be resolved solely through technical methodological improvements; it requires the transformation of the teacher-student relationship from a transactional and punitive nature to one that is relational, appreciative, and dialogical. The integration of values such as love (maḥabbah), empathy, and the creation of a psychologically safe space within the Love-Based Curriculum theoretically proves capable of suppressing stress hormones and lowering students' affective filters. In conclusion, through the pedagogy of love, language errors are positioned as a natural process of linguistic development, thereby transforming Arabic language learning into a humanizing, inclusive, and intimidation-free experience.